PENGARUH PERINGKAT OBLIGASI DAN KONFLIK BONDHOLDER-SHAREHOLDER TERHADAP PENERAPAN KONSERVATISME AKUNTANSI - Mailiza Maharani; Agrianti Komalasari; Komaruddin Komaruddin (Faculty of Economics and Business, 2021)
This research is a research using quantitative analysis that aims to know the influence of bond rating and bondholder-shareholder conflicts to accounting conservatism implementation in non finance and banking companies that listed in the Indonesian Stock Exchange (IDX) in 2011-2018. The data which is used in this research is secondary data obtained from company’s annual report in Indonesian Stock Exchange (IDX). The samples of this research obtained by using purposive sampling method. Based on this criteria, obtained 33 companies as sample of this research. Analysis method which is used is the multiple regressions analysis. The result of this research indicate that bond rating and bondholder-shareholder conflict have no significant effect on accounting conservatism implementation.